Oblique angle deposition of HfO2 thin films: quantitative assessment of indentation modulus and micro structural properties. (3rd March 2015) - Tokas, R B; Jena, S; Sarkar, P; Polaki, S R; Thakur, S; Basu, S; Sahoo, N K
Abstract: Oblique angle deposition of oxides is used routinely for fabricating inhomogeneous thin films with proven correlation between refractive index and the angle of deposition. Inhomogeneous layers play a key role in the development of rugate interference devices for photo-physical applications. Such obliquely deposited thin films show high porosity which is a critical issue related to their density, mechanical and environmental stability. Hence, it is important to investigate elastic properties of such film in addition to optical properties. Using atomic force acoustic microscopy, we report indentation modulus of HfO2 thin films deposited at angles 80, 68, 57, 40 and 0 degree with normal to substrate plane on Si (100) substrate. Such films were measured to have indentation modulus of 42 GPa for extreme obliquely deposited film and indentation modulus increases with decrease in angle to become highest with a value of 221 GPa for normally deposited films. We also report microstructural properties and density of films measured by FESEM and grazing angle x-ray reflectometer, respectively. Both indentation modulus and density depict a nonlinearly decreasing behavior with angle of deposition. Variation of density is again confirmed from FESEM cross-sectional morphology.